Dinamika Populasi Kompleks Parasitoid Telur Helicoverpa armigera (Hubner) Pada Ekosistem Kapas Monokultur dan Kapas Tumpangsari dengan Jagung - Damayanti BUCHORI; Bandung SAHARI; Dwi Adi SUNARTO (Jurnal Pengendalian Hayati, 2008)
Eggs of Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) on its host plants could beparasitized by some species of parasitoids, especially of the genus Trichogrammatoidea andTrichogramma. This research was aimed to study the population dynamics of egg parasitoids of H.armigera on unsprayed fields of cotton monoculture and intercropped with maize. The plot size ofeach field was 19 m x 20 m, with five replicates. We collected H. armigera eggs from both fieldsperiodically since 23 days after planting (dap) to 100 dap. The eggs were collected on 9 sample units(size of sample unit: 1 m2) in 7-days interval. The number of collected and parasitized eggs wasrecorded and the emerged parasitoids were identified to species level. The result showed that thefluctuation pattern of H. armigera egg population was not different on cotton monoculture and cottonintercropped with maize. The parasitoid population was relatively high during the flowering phase ofcotton and maize. The parasitoids of H. armigera eggs found in cotton monoculture and cottonintercropped with maize were T’toidea armigera, T’toidea guamensis, T’toidea bactrae bactrae,T’toidea bactrae fumata, T. chilonis and T. chilotraeae . The dominant species on early season untilthe flowering phase of the plants was T’toidea armigera, while on the latter phase of the plantphenology was T. chilotraeae. Implication of this population dynamics and the succession of theparasitoids in biological control are discussed.